تأثير تمرينات الألعاب الجانبية الصغيرة في المهارات المركبة للاعبي كرة القدم بأعمار (١٣-١٤) سنة - البرزنجي, أ.د. ناظم جبار جلال; صوفي, م.م. كيفي على (Sulaimani Journal for Humanities, 2023)
The research aims to prepare small side games exercises at ages (13-14) years and to identify the effect of small side games exercises on the number of compound skills at ages (13-14) years for the experimental and control groups and to identify the differences in compound skills at ages (13-14) years in Post-tests between the experimental and control groups. The researcher used the experimental approach due to its suitability to the nature of the problem, and the research community chose the intentional method, and they are the players of the Specialized School of Football for the Brusk Sports Club, ages (13-14) years from the (2021-2022) season, and their number is (65) players, and the research sample was (38) Players, so the size of the research sample was (24) players. The sample was divided into two control and experimental groups in a random manner and by lottery method. Each group consisted of (12) players. The control group trained the traditional curriculum prepared by the team coach, while the experimental group trained the training curriculum prepared by the researcher. The curriculum was applied with exercises at the beginning of the main section of the unit, at the of three training units per week for a period of (8) weeks, and the total number of training units (24) units, and for the purpose of processing the results, the researcher used the SPSS statistical bag. As for the conclusions reached by the researcher: Small side games exercises applied by the experimental group showed a positive effect in improving the results of the post tests and in all the compound skills under study. As for the recommendations, the researcher recommends applying the small side games program to players of the age groups in the Kurdistan region of Iraq in order to improve the physical and skill performance requirements of football for the age group (13-14) years